Buddha in Africa - Schafer, Nicole (South Africa ; Sweden : CAT&Docs, 2019)
Enock Alu is a teenager growing up in a Chinese Buddhist orphanage in Malawi who feels torn between his African roots and Chinese upbringing. With dreams of becoming a martial arts hero like Jet Li, Enock, in his final year of school, has to make some tough decisions about his future: Will he return to his relatives in his home village or study abroad in Taiwan? Set against China’s expanding influence on the continent, Buddha in Africa provides a unique insight into the forces of cultural soft power on the identity and imagination of children growing up between two cultures.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films